Police culture: individual and organizational differences in police officer perspectives. Issue 1 (20th March 2017) - Cordner, Gary
Abstract : Purpose: Much of the commentary about police culture treats it as a monolithic and problematic feature of the police occupation that inhibits change and progress. The purpose of this paper is to draw on surveys completed by over 13, 000 sworn police to describe officers' occupational outlooks and explore the extent to which they vary across individuals and police agencies. Design/methodology/approach: This paper draws upon employee survey data from 89 US police and sheriff departments collected in 2014-2015 to examine police culture through officers' views of the community, police work, and police administration and to explore the extent to which these beliefs and opinions are affected by personal characteristics and organizational affiliation. Findings: Results indicate that officers' perspectives are more positive than might be expected and do not vary greatly by officer personal characteristics. They differ more substantially across police agencies. This suggests that police culture is to a significant extent an organizational phenomenon, not simply an occupational one. Originality/value: Examining the views and perspectives of over 13, 000 sworn police employed in 89 different police organizations provides a more representative and generalizable picture of police culture than previous studies that typically analyzed officers in only one police department.